Coronavirus Disease (COVID-19) pada Pasien Hemodialisis - Ellyana Firdaus; Okti Sri Purwanti (Jurnal Kesehatan Terpadu (Integrated Health Journal), 2020)
Hemodialysis is a treatment for patients with terminal stage chronic renal failure, kidney function is replaced by a device called a dyalizer. Patients undergoing hemodialysis may be at higher risk for infection with COVID-19 due to frequent repetitive physical presence in health care facilities and physical closeness of patients during hemodialysis. The purpose of this case study is to describe the management of hemodialysis patients infected with the coronavirus disease 2019 (COVID-19). The method used in this research is descriptive with an exploratory research design. Database searches are taken from review literature, literature is obtained by keyword searches using sources such as Springer Link, Cambridge, Nature.com, Ebsco, Proquest and Google Scholar. Management of hemodialysis patients infected with COVID-19, namely screening at the beginning when the patient arrived with a temperature check, wearing a mask, and exposure to epidemic areas and the readiness of patients and health workers such as use of complete PPE, hand hygiene, correct cough etiquette. Management of patients and health workers during hemodialysis is appropriate initial treatment such as screening patients, when hemodialysis is performed, patients are spaced apart if necessary, isolation rooms, after completion of hemodialysis treatment the patient and the room must be disinfected.